“O obscurantismo salazarista”: exílio, periodismo e intelectualidade (Barradas de Carvalho/ SP, 1964-1970) - Conceição, Thaís Teixeira Dias da (2016)
This work analyses through the journal Portugal Democrático the intellectual and culture repression practiced by the Portuguese authoritarian government. In Portugal, in the 28 th may 1926, has been instaured an authoritarian government, that some years later has become the Estado Novo and has had Antônio de Oliveira Salazar as it´s leader. His repressive politics have lead many of his opponents to leave the country. Between these emigrants many have chosen Brazil as destination. This way one have formed an oppositionist colony that gathered have originated Portugal Democrático, one of the most important oppositionist journals to Salazar´s government in the world. In between the many articles published in the journal the subject of culture and intellectuals have had special attention. Joaquim Barradas de Carvalho, was one of these political immigrants who collaborated with the periodic between from 1964 to 1970. In his block “O Obscurantismo Salazarista” have given special attention to the repression to culture and intellectuality. These articles were what birthed this dissertation, addressing issues such as repression the Portugueses Universities, the pursuit of academics, and the closing of the Portuguese society of writers and some of the intellectuals persecuted by Salazar. Criticizing the authoritarian Portuguese Government attitudes